Pedestrians’ Speed Analysis for Two-Stage Crossing at a Signalized Intersection - Guo, Yongqing; Wang, Xiaoyuan; Meng, Xinqiang; Wang, Jie; Liu, Yaqi (Civil Engineering Journal, 2019)
Pedestrian walking speed is an important and essential parameter for designing traffic signals at signalized intersections. However, there is a lack of understanding of pedestrian speed characteristics in a twice crossing. This paper focuses on analyzing the differences of pedestrians’ crossing speeds between the two stages, and identifying the major factors affecting the speed changes. Pedestrians were classified by age, gender and group size, and pedestrians’ speed characteristics of each group were analyzed. Besides, each age group were divided into five categories by gender and group size, and the effect sizes of gender and group size on speed-changing at the two stages were examined. The results show significant differences in walking speed on different gender and age groups, as well as on different group size. The young group has different factors affecting the speed change in the two directions, and the middle-aged and old groups have same factors affecting the speed change in the two directions. This study proposed a goal–oriented and time-driven behavior model for pedestrian two-stage crossing at signalized intersections, where the two directions have different pedestrian signal timing. The results also show that the proposed model is effective in simulating pedestrian speed characteristics of twice crossing. This research provides a theoretical basis for identifying pedestrian movement intention, optimizing signal timing, and improving pedestrian infrastructure at signalized intersections.